Could VGF and/or its derived peptide act as biomarkers for the diagnosis of neurodegenerative diseases: A systematic review - Alqarni, Saleha; Alsebai, Mashael (Frontiers in Endocrinology, 2022)
Background: The increasing ageing population has led to an increase in the prevalence of neurodegenerative diseases, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS). However, as yet, there are no simple biomarkers to predict the onset of such diseases. Recently, VGF and its peptides have been highlighted in neurodegenerative diseases. VGF (non-acronymic) is a polypeptide induced in PC12 cells by neurotrophic factors and VGF mRNA is extensively expressed in the brain, peripheral endocrine tissues, and the gastrointestinal tract. VGF precursors are processed into several smaller peptides that have specific biological activities. Objective: This systematic review aimed to determine whether VGF and/or its derived peptides can be used as biomarkers for the diagnosis of ALS, PD, and AD, specifically, (1) the level of VGF and/or its derived peptides, (2) amyloid-beta, (3) dopamine, and (4) cognitive score. Methodology: A search was undertaken in the Ovid EMBASE, Cochrane Library, PubMed, Scopus, and Web of Science for observational studies. Publications that assessed the level of VGF and/or its derived peptides among people with neurodegenerative diseases and compared them with healthy people were included. The quality of the included studies was assessed using the National Heart, Lung, and Blood Institute Quality Assessment Tool. Result: A search of the databases yielded 834 studies, of which, eight observational studies met the inclusion criteria with a total of 673 participants (51.7% males) aged >18 years. Seven studies showed significant decreases in VGF and its derived peptides in adults with AD, PD, and ALS compared to healthy controls (p<0.05). However, one study showed that there was no significant difference in VGF in AD compared to healthy control(p>0.05). Furthermore, only one study reported that VGF was positively associated with dopamine but not with Aβ1-42, and low levels of VGF were linked to cognitive deficits. Conclusion: The use of VGF and its derivatives for the diagnosis of PD, ALS, AD remains unclear, so further investigation of the role of VGF in neurodegenerative diseases and pathophysiology is needed to provide new insights.